Naravne nesreče, ki so najpogosteje prizadele območje Slovenije od konca 19. stoletja do leta 1990 - Dobaja, Dunja (Časopis za zgodovino in narodopisje, 2022)
Based on scientific literature, archival sources and newspapers, this article outlines the most frequent natural disasters that Slovenia has faced in different historical periods, noting that Slovenia has been, and still is, primarily a flood and earthquake-prone area. It traces the different practices of preventive coping with natural disasters and the understanding of natural disasters in the context of the authorities of the time, but with a focus on the period between the two wars, which is the primary period of the author’s research interest. The article does not deal with the period of the Second World War, as this requires special coverage.
Keywords: elementarne nesreče; naravne nesreče; Slovenija; zgodovina; zgodovinski pregledi